The impact of the COVID-19 pandemic on global industrial production - Steven B. Kamin; John Kearns (American Enterprise Institute (AEI), 2021)
This paper describes one of the first attempts to gauge the effect of the COVID-19 pandemic on the global trajectory of a key measure of economic activity – industrial production – over the course of 2020. It is also among the first efforts to distinguish between the role of domestic variables and global trade in transmitting the economic effects of COVID-19.
Keywords: A; 330; Coronavirus; Economic Policy; Global Economy; Trade Policy